Antifungal Effect of Leaf Extracts on the Groundnut Late Leaf Spot Pathogen Cercosporidium personatum - Putranto, Dwiyandito Ikhsan; Kasiamdari, Rina Sri (Universitas Gadjah Mada, 2024)
Late leaf spot of groundnut is caused by the fungal pathogen of Cercosporidium personatum. Efforts to prevent this disease generally use synthetic fungicides that can cause environmental pollution. This study aims to identify the fungal pathogen of groundnut late leaf spot and study the antifungal effect of leaf extract of some plants for leaf spot intensity suppression. Late leaf spot pathogen was identified based on morphological characteristics of hyphae and conidia. The leaf extracts of butterfly pea (Clitoria ternatea), Mexican sunflower (Tithonia diversifolia), basil (Ocimum gratissimum), and sugar apple (Annona squamosa) at a concentration of 25% against C. personatum were evaluated in vitro based on growth inhibition. The growth and intensity of groundnut disease attacks were assessed for seven weeks by inoculating C. personatum and application of the leaf extracts. Results showed that the pathogen was identified as C. personatum with conidia characteristics of cylindrical to obclavate, short and slightly curved with four septa, and 35.75 × 7.11 µm in size. The percentage of inhibition of C. personatum in vitro reached 94.03% by leaf extract of C. ternatea, 88.56% by T. diversifolia, 87.20% by O. gratissimum, and 84.10% by A. squamosa. Treatment of C. ternatea increased plant height up to 12.85% and reduced the most optimal percentage of the infected leaves up to 61.53%. C. ternatea leaf extract was found to be the most effective extract to suppress C. personatum infection by 77.94%, while T. diversifolia, O. gratissimum, and A. squamosa reduced disease severity by 70.15%, 65.43%, and 57.76%, respectively.